Semirational design and engineering of grapevine glucosyltransferases for enhanced activity and modified product selectivity - Joshi, Rakesh; Trinkl, Johanna; Haugeneder, Annika; Haertl, Katja; Franz-Oberdorf, Katrin; Giri, Ashok; Hoffmann, Thomas; Schwab, Wilfried (Glycobiology, 2019)
Uridine diphosphate-dependent glycosyltransferases (UGTs) catalyze the transfer of a diversity of sugars to several acceptor molecules and often exhibit distinct substrate specificity. Modulation of glycosyltransferases for increased catalytic activity and altered substrate or product specificity are the key manipulations for the biotechnological use of glycosyltransferases in various biosynthetic processes. Here, we have engineered the binding pocket of three previously characterized Vitis vinifera glycosyltransferases, UGT88F12, UGT72B27 and UGT92G6, by structure-guided in silico mutagenesis to facilitate the interactions of active site residues with flavonol glucosides and thus modify substrate specificity and activity. Site-directed mutagenesis at selected sites, followed with liquid chromatography-mass spectrometry based activity assays, exhibited that mutant UGTs were altered in product selectivity and activity as compared to the wild-type enzymes. Mutant UGTs produced larger amounts of flavonol di-monosaccharide glucosides, which imply that the mutations led to structural changes that increased the volume of the binding pocket to accommodate a larger substrate and to release larger products at ease. Mutants showed increased activity and modified product specificity. Thus, structure-based systematic mutations of the amino acid residues in the binding pocket can be explored for the generation of engineered UGTs for diverse biotechnological applications.
Keywords: flavonol; Glycosyltransferase; in silico analysis; Mutagenesis; selectivity